2002
DOI: 10.1074/jbc.m108890200
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Receptor Activation Regulates GnRH Gene Expression and Secretion in GT1–7 GnRH Neurons

Abstract: Melatonin plays a significant role in the control of the hypothalamic-pituitary-gonadal axis. Using the GT1-7 cell line, an in vitro model of GnRH-secreting neurons of the hypothalamus, we examined the potential signal transduction pathways activated by melatonin directly at the level of the GT1-7 neuron. We found that melatonin inhibits forskolin-stimulated adenosine 3-, 5-cyclic monophosphate accumulation in GT1-7 cells through an inhibitory G protein. Melatonin induced protein kinase C activity by 1.65-fold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
69
2
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(80 citation statements)
references
References 70 publications
6
69
2
3
Order By: Relevance
“…Previous studies have shown that ERK1/2 is activated by phosphorylation in response to melatonin, leading to attenuation of neuronal cell damage by ischemic injury [7]. Also, melatonin increases ERK1/2 phosphorylation levels in neuronal cell cultures [18]. This study demonstrated that the levels of ERK1/2 up-stream enzymes, phospho-Raf-1 and phospho-MEK1/2, decrease in cases of brain injury, and melatonin prevented the dephos- phorylation of these kinases.…”
Section: Discussionmentioning
confidence: 49%
“…Previous studies have shown that ERK1/2 is activated by phosphorylation in response to melatonin, leading to attenuation of neuronal cell damage by ischemic injury [7]. Also, melatonin increases ERK1/2 phosphorylation levels in neuronal cell cultures [18]. This study demonstrated that the levels of ERK1/2 up-stream enzymes, phospho-Raf-1 and phospho-MEK1/2, decrease in cases of brain injury, and melatonin prevented the dephos- phorylation of these kinases.…”
Section: Discussionmentioning
confidence: 49%
“…Night work and artificial light at night may affect human physiology, introducing changes in the regulation of the circadian rhythm, with a reduction of melatonin synthesis and changes in the profiles of other hormones. Some speculations point to an interrelation between melatonin and E2, which results in decreased melatonin synthesis leading to an increase in E2 concentration (40)(41)(42). It has been hypothesized that women working night shifts for many years may have up-regulated hypothalamic gonadal axis (with increase of circulating estrogenes) as a result of decreased melatonin (43).…”
Section: Discussionmentioning
confidence: 99%
“…The pulsatile secretion of gonadotropin-releasing hormone (GnRH), from a small number of neurons in the hypothalamus, controls luteinizing hormone and follicle-stimulating hormone secretion, which, in turn, regulates the functional activity of gonads (Glass & Knotts 1987;Kennaway & Rowe 1995). Melatonin has been shown to downregulate GnRH gene expression in a cyclical pattern over a 24-h period (Roy & Belsham 2002).…”
Section: Melatoninmentioning
confidence: 99%